Sweat-proof quick-dry textile containing silver ion antibacterial agent and preparation method of sweat-proof quick-dry textile
By modifying titanium dioxide, fiber-forming resin and nano-silver antibacterial powder, sweat-resistant quick-drying textiles containing silver ion antibacterial agents were prepared, which solved the problem of poor antibacterial properties and ultraviolet resistance in existing textiles, and achieved excellent performance of textiles and the comfort and protection needs of athletes.
Patent Information
- Application Number
- CN202411713757.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing sweat-proof quick-drying textiles are not ideal in terms of antibacterial properties and UV resistance, and cannot meet the needs of tennis players.
By preparing methods of modified titanium dioxide, modified fiber resin and modified nano-silver antibacterial powder, anti-sweat-proof quick-drying textiles containing silver ion antibacterial agents were prepared. Modified titanium dioxide improves the UV resistance of textiles, modified fiber resin enhances the breaking strength of textiles, and modified nano-silver antibacterial powder improves the antibacterial effect of textiles.
It achieves excellent UV resistance, antibacterial, moisture permeability and tensile strength effects of textiles, meeting the needs of tennis players for comfort and protection.
Smart Images

Figure BDA0005156404990000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of textiles, and in particular relates to a sweat-proof quick-drying textile containing a silver ion antibacterial agent and a preparation method thereof. Background Art
[0002] As one of the three main synthetic fibers, polyester fiber is widely used in clothing fabrics and other non-clothing fields due to its excellent physical and chemical properties. For people who often exercise or engage in outdoor activities, sweat-proof and quick-drying polyester textiles can help them keep their bodies dry, reduce the discomfort caused by sweat, and thus improve athletic performance.
[0003] With the development of tennis in my country, the design and production of tennis clothing need to meet multiple requirements to ensure that athletes can maintain optimal comfort, flexibility and performance during competition and training. Polyester fiber textiles are widely used in various fields due to their excellent physical and chemical properties, but the hygroscopicity of polyester fiber itself is poor, which easily causes the skin to feel damp and uncomfortable after sweating when worn. In the prior art, polyester fiber is usually blended with natural fibers (such as cotton and linen) or synthetic fibers with good hygroscopicity (such as modal and lyocell) to improve the overall hygroscopicity, but the effect is not ideal.
[0004] Chinese patent application No. 202010765566.9 provides a new type of sweat-proof fabric, including a surface waterproof layer and a close-fitting moisture-absorbing and breathable layer, wherein the surface waterproof layer is woven from waterproof yarns blended from polyester fiber and cotton fiber, and the close-fitting moisture-absorbing and breathable layer is woven from moisture-absorbing and breathable yarns blended from polyester fiber, bamboo fiber and Tencel fiber. The surface has high water resistance and plays a role in preventing sweat, and the close-fitting surface has excellent moisture absorption performance, can quickly and massively absorb sweat from the human body surface, remove sweat, enhance the human body's comfort, and meet people's use needs. However, the fabric has poor antibacterial properties and does not have anti-ultraviolet effects, and cannot meet the needs of consumers.
[0005] Therefore, there is an urgent need for a sweat-proof quick-drying textile containing a silver ion antibacterial agent and a preparation method thereof. Summary of the invention
[0006] The purpose of the present invention is to provide a sweat-proof quick-drying textile containing a silver ion antibacterial agent and a preparation method thereof.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a sweat-proof quick-drying textile containing a silver ion antibacterial agent comprises the following steps:
[0009] (1) Preparation of modified polyester fiber:
[0010] The preparation method of modified polyester fiber comprises the following steps:
[0011] S1: Blending modified titanium dioxide, modified nano silver antibacterial powder and polyethylene terephthalate I in a weight ratio of (2-3): (1-2): 15 at a blending temperature of 260-265° C., extruding with a screw extruder at an extrusion temperature of 200-210° C. and a screw speed of 100-200 rpm, and pelletizing to obtain a modified masterbatch;
[0012] S2: blending the modified masterbatch and the modified fiber-forming resin in a weight ratio of (2-5):100, spinning, and obtaining modified polyester fibers;
[0013] (2) Modified polyester fiber and cotton fiber are blended in a weight ratio of 100:(35-45) to obtain blended yarn, and the blended yarn is used as warp yarn and weft yarn for weaving to obtain sweat-proof quick-drying textiles containing silver ion antibacterial agent.
[0014] Furthermore, the yarn count of the blended yarn is 50S, wherein the warp yarn density is 130-150 yarns / inch, and the weft yarn density is 55-60 yarns / inch.
[0015] Furthermore, the spinning conditions are: spinning temperature 270-300°C, spinning speed 2500-3500 m / min,
[0016] Furthermore, the preparation method of the modified titanium dioxide comprises the following steps:
[0017] S1: Mix titanium dioxide, ethanol aqueous solution and silane coupling agent KH570 in a weight ratio of 1: (10-15): (0.02-0.05), stir at 50-60° C. for 3-5 hours, filter, wash and dry to obtain silane-modified titanium dioxide;
[0018] S2: Mix silane-modified titanium dioxide, epoxy fatty acid methyl ester and ethyl acetate in a weight ratio of 1:(0.2-0.4):(3-4), heat to 76-78°C for reaction for 1-2h, filter, wash with anhydrous ethanol 2-3 times, and dry to obtain modified titanium dioxide.
[0019] Furthermore, the titanium dioxide comprises titanium dioxide A, titanium dioxide B and titanium dioxide C in a weight ratio of (0.3-0.5):1:(1.3-1.6); the particle size of titanium dioxide A is 2-7 nm, and the specific surface area is 20-30 m 2 / g; the particle size of titanium dioxide B is 10-15nm, and the specific surface area is 30-40m 2 / g; the particle size of titanium dioxide C is 50-60nm, and the specific surface area is 40-50m 2 / g.
[0020] Tennis matches are usually played outdoors, especially in the summer when the sun is strong. Prolonged exposure to ultraviolet rays can cause sunburn, sun spots and even increase the risk of skin cancer. The anti-ultraviolet function can effectively block ultraviolet rays and protect the skin of athletes. However, the anti-ultraviolet effect of tennis clothing currently on the market is not ideal. The present invention attempts to add commercially available titanium dioxide to improve the anti-ultraviolet effect of textiles, but the effect is not ideal. The anti-ultraviolet effect of textiles can be improved by modifying commercially available titanium dioxide. Analysis shows that titanium dioxide is an efficient photocatalyst that can absorb ultraviolet rays and convert them into other forms of energy, and titanium dioxide is modified by epoxy fatty acid methyl ester to improve its dispersibility in the system, and can also react with the hydroxyl groups in polyester fibers to form a stable network structure, thereby improving the stability of the entire system.
[0021] Furthermore, the preparation method of the modified fiber-forming resin comprises the following steps: mixing 6 parts by weight of polyethylene terephthalate II, 30-35 parts by weight of m-methylphenol and 1-1.5 parts by weight of a modifier, stirring and reacting at 30-35° C. for 50-60 minutes to obtain a modified fiber-forming resin.
[0022] Furthermore, the modifier is glycidyl methacrylate, maleic anhydride and isocyanate in a weight ratio of 1:(1.4-1.6):(0.2-0.5).
[0023] Tennis is a high-intensity sport with a large range of motion, which requires a higher breaking strength to ensure the life of the clothes. The present invention can improve the breaking strength of textiles by modifying the fiber-forming resin. Analysis shows that glycidyl methacrylate, maleic anhydride and isocyanate contain epoxy groups, anhydride groups and isocyanate groups respectively, and these active functional groups can react chemically with the hydroxyl groups or other active groups at the ends of the polyethylene terephthalate II molecular chains to form covalent bonds. The formation of these covalent bonds can enhance the crosslinking between polyethylene terephthalate II molecules to form a more stable three-dimensional network structure. This crosslinked network can effectively disperse external forces and improve the overall strength and toughness of the fiber. At the same time, the active functional groups can react with the hydroxyl groups at the ends of the polyethylene terephthalate II molecular chains to improve the interface compatibility between the modifier and the polyethylene terephthalate II matrix.
[0024] In high-intensity tennis matches, athletes will sweat a lot, and sweat will have an adverse effect on athletic performance and comfort. The present invention can improve the anti-ultraviolet effect after washing when using a specific ratio of glycidyl methacrylate, maleic anhydride and isocyanate and titanium dioxide with specific parameters. Analysis shows that under this condition, titanium dioxide is more evenly dispersed, and the modified titanium dioxide further undergoes cross-linking reaction with hydroxyl groups or other active groups in polyester fibers to form a stable cross-linking network, so that titanium dioxide is firmly attached to the fiber surface. At the same time, the moisture permeability of the textile under this condition is better.
[0025] Furthermore, the preparation method of the modified nano silver antibacterial powder comprises the following steps:
[0026] (1) mixing nano silver antibacterial powder, silane coupling agent KH550, ethanol and deionized water, heating and stirring at 70-75° C. for 2-3 hours, cooling, filtering and washing to obtain silane-modified powder;
[0027] (2) Mixing silane-modified powder, nano-polytetrafluoroethylene, polyvinyl alcohol and 45-50% by weight ethanol aqueous solution in a weight ratio of 1: (10-15): (0.1-0.4): (60-80), dispersing them uniformly, and then spray drying them to obtain modified nano-silver antibacterial powder.
[0028] Furthermore, the weight ratio of the nano silver antibacterial powder, the silane coupling agent KH550, ethanol and deionized water is 1: (0.2-0.4): (15-20): (30-35).
[0029] Due to the high sweating, the tennis players' clothes need better antibacterial properties. The commercially available nano silver antibacterial powder has poor dispersibility in the system of the present invention, and the antibacterial effect is not ideal. The present invention improves the antibacterial effect of textiles by modifying the nano silver antibacterial powder. Nano polytetrafluoroethylene has excellent chemical resistance and heat resistance, and can form a protective film on the surface of polyester fiber to prevent nano silver from being worn or falling off during the washing process. At the same time, polyvinyl alcohol has good film-forming properties, and can form a uniform film on the surface of polyester fiber to fix nano silver and PTFE and improve the stability of the antibacterial effect. Polyvinyl alcohol can generate hydrogen bonds or van der Waals forces with hydroxyl groups or other active groups on the surface of polyester fiber, further enhancing the adhesion of nano silver on the fiber surface.
[0030] The invention also provides sweat-proof quick-drying textiles containing silver ion antibacterial agent prepared by the preparation method.
[0031] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0032] 1. The present invention can improve the anti-ultraviolet effect of textiles by modifying titanium dioxide.
[0033] 2. The present invention can improve the breaking strength of textiles by modifying the fiber-forming resin.
[0034] 3. When using a specific ratio of glycidyl methacrylate, maleic anhydride and isocyanate and specific parameters of titanium dioxide, the anti-ultraviolet effect after washing can be improved; at the same time, the moisture permeability of textiles is better under this condition.
[0035] 4. The present invention improves the antibacterial effect of textiles by modifying the nano-silver antibacterial powder. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The raw materials used in the following examples of the present invention are all commercially available products:
[0038] Nano silver antibacterial powder, Fujian Ruisen New Materials Co., Ltd., model RS-kj03.
[0039] Polyethylene terephthalate I was purchased from Zhejiang Guxiandao Green Fiber Co., Ltd., fiber-grade low-viscosity polyester chips with an intrinsic viscosity of 0.68 dl / g.
[0040] Epoxy fatty acid methyl ester, CAS: 6084-76-0, was purchased from Zibo Lishuo Chemical Trading Co., Ltd.
[0041] m-Cresol, CAS: 203-577-9.
[0042] The density of the polyethylene terephthalate II is 1.4 g / cm 3 , purchased from MDI Company, USA, model number PET-930FG.
[0043] Nano polytetrafluoroethylene, Guangzhou Yinuo Chemical Technology Co., Ltd., JYN815.
[0044] Polyvinyl alcohol, Kaimaoxing (Hebei) Cellulose Co., Ltd., PVA2488.
[0045] Cotton fiber, Dezhou Caishihe Textile Co., Ltd., kapok fiber.
[0046] Example 1
[0047] This embodiment provides a sweat-proof quick-drying textile containing a silver ion antibacterial agent, and a preparation method thereof comprises the following steps:
[0048] (1) Preparation of modified polyester fiber:
[0049] The preparation method of modified polyester fiber comprises the following steps:
[0050] S1: Blending modified titanium dioxide, modified nano silver antibacterial powder and polyethylene terephthalate I in a weight ratio of 2.5:1.6:15 at a blending temperature of 262°C, extruding with a screw extruder at an extrusion temperature of 210°C and a screw speed of 150rpm, and pelletizing to obtain a modified masterbatch;
[0051] S2: blending the modified masterbatch and the modified fiber-forming resin in a weight ratio of 3:100, and spinning the mixture under the following conditions: spinning temperature of 280°C and spinning speed of 3000 m / min, to obtain modified polyester fiber;
[0052] (2) Modified polyester fiber and cotton fiber are blended in a weight ratio of 5:2 to obtain blended yarn, and the blended yarn is used as warp yarn and weft yarn for weaving. The yarn count of the blended yarn is 50S, wherein the warp yarn density is 140 yarns / inch, and the weft yarn density is 58 yarns / inch, to obtain an anti-perspirant quick-drying textile containing a silver ion antibacterial agent.
[0053] The preparation method of the modified titanium dioxide comprises the following steps:
[0054] S1: titanium dioxide, 60wt% ethanol aqueous solution and silane coupling agent KH570 in a weight ratio of 1:12:0.04 were mixed, stirred at 55°C for 4h, filtered, washed and dried to obtain silane-modified titanium dioxide;
[0055] S2: Mix silane-modified titanium dioxide, epoxy fatty acid methyl ester and ethyl acetate in a weight ratio of 1:0.3:3.5, heat to 77°C for reaction for 1.5 hours, filter, wash with anhydrous ethanol three times, and dry to obtain modified titanium dioxide.
[0056] Titanium dioxide includes titanium dioxide A, titanium dioxide B and titanium dioxide C in a weight ratio of 0.4:1:1.5; the particle size of titanium dioxide A is 2-7nm and the specific surface area is 20-30m 2 / g; the particle size of titanium dioxide B is 10-15nm, and the specific surface area is 30-40m 2 / g; the particle size of titanium dioxide C is 50-60nm, and the specific surface area is 40-50m 2 / g. Purchased from Beijing Dekedao Gold Technology Co., Ltd.
[0057] The preparation method of the modified fiber-forming resin comprises the following steps: 6 parts by weight of polyethylene terephthalate II, 32 parts by weight of m-methylphenol and 1.2 parts by weight of a modifier are mixed, and stirred at 32° C. for 55 minutes to obtain the modified fiber-forming resin.
[0058] The modifier is glycidyl methacrylate, maleic anhydride and isocyanate in a weight ratio of 1:1.5:0.4.
[0059] The preparation method of the modified nano silver antibacterial powder comprises the following steps:
[0060] (1) mixing nano silver antibacterial powder, silane coupling agent KH550, ethanol and deionized water in a weight ratio of 1:0.3:17:32, heating and stirring at 72° C. for 2.5 h, cooling, filtering and washing to obtain silane-modified powder;
[0061] (2) Silane-modified powder, nano-polytetrafluoroethylene, polyvinyl alcohol and 48% by weight ethanol aqueous solution are mixed in a weight ratio of 1:13:0.3:70, dispersed evenly, and then spray-dried to obtain modified nano-silver antibacterial powder.
[0062] Example 2
[0063] This embodiment provides a sweat-proof quick-drying textile containing a silver ion antibacterial agent, and a preparation method thereof comprises the following steps:
[0064] (1) Preparation of modified polyester fiber:
[0065] The preparation method of modified polyester fiber comprises the following steps:
[0066] S1: Blending modified titanium dioxide, modified nano silver antibacterial powder and polyethylene terephthalate I in a weight ratio of 2:2:15 at a blending temperature of 260°C, extruding with a screw extruder at an extrusion temperature of 200°C and a screw speed of 200 rpm, and pelletizing to obtain a modified masterbatch;
[0067] S2: blending the modified masterbatch and the modified fiber-forming resin in a weight ratio of 1:50, and spinning the mixture under the following conditions: spinning temperature of 280° C. and spinning speed of 3000 m / min, to obtain modified polyester fiber;
[0068] (2) Modified polyester fiber and cotton fiber are blended in a weight ratio of 5:2 to obtain blended yarn, and the blended yarn is used as warp yarn and weft yarn for weaving. The yarn count of the blended yarn is 50S, wherein the warp yarn density is 140 yarns / inch, and the weft yarn density is 58 yarns / inch, to obtain an anti-perspirant quick-drying textile containing a silver ion antibacterial agent.
[0069] The preparation method of the modified titanium dioxide comprises the following steps:
[0070] S1: titanium dioxide, 60wt% ethanol aqueous solution and silane coupling agent KH570 in a weight ratio of 1:10:0.05 were mixed, stirred at 60°C for 5h, filtered, washed and dried to obtain silane-modified titanium dioxide;
[0071] S2: Mix silane-modified titanium dioxide, epoxy fatty acid methyl ester and ethyl acetate in a weight ratio of 1:0.2:4, heat to 76°C for reaction for 2 hours, filter, wash with anhydrous ethanol three times, and dry to obtain modified titanium dioxide.
[0072] Titanium dioxide includes titanium dioxide A, titanium dioxide B and titanium dioxide C in a weight ratio of 0.5:1:1.3; the particle size of titanium dioxide A is 2-7nm and the specific surface area is 20-30m 2 / g; the particle size of titanium dioxide B is 10-15nm, and the specific surface area is 30-40m 2 / g; the particle size of titanium dioxide C is 50-60nm, and the specific surface area is 40-50m 2 / g. Purchased from Beijing Dekedao Gold Technology Co., Ltd.
[0073] The preparation method of the modified fiber-forming resin comprises the following steps: 6 parts by weight of polyethylene terephthalate II, 32 parts by weight of m-methylphenol and 1.2 parts by weight of a modifier are mixed, and stirred at 32° C. for 55 minutes to obtain the modified fiber-forming resin.
[0074] The modifier is glycidyl methacrylate, maleic anhydride and isocyanate in a weight ratio of 1:1.4:0.5.
[0075] The preparation method of the modified nano silver antibacterial powder comprises the following steps:
[0076] (1) mixing nano silver antibacterial powder, silane coupling agent KH550, ethanol and deionized water in a weight ratio of 1:0.2:15:30, heating and stirring at 70° C. for 2 h, cooling, filtering and washing to obtain silane-modified powder;
[0077] (2) Silane-modified powder, nano-polytetrafluoroethylene, polyvinyl alcohol and 50% by weight ethanol aqueous solution are mixed in a weight ratio of 1:10:0.4:80, dispersed evenly, and then spray-dried to obtain modified nano-silver antibacterial powder.
[0078] Comparative Example 1
[0079] The difference between this comparative example and Example 1 is that the preparation method of the modified titanium dioxide comprises the following steps: mixing titanium dioxide, 60wt% ethanol aqueous solution and silane coupling agent KH570 in a weight ratio of 1:12:0.04, stirring and reacting at 55°C for 4h, filtering, washing and drying to obtain modified titanium dioxide.
[0080] Comparative Example 2
[0081] The difference between this comparative example and Example 1 is that the titanium dioxide comprises titanium dioxide A, titanium dioxide B and titanium dioxide C in a weight ratio of 1:1:1; the particle size of titanium dioxide A is 2-7 nm, and the specific surface area is 20-30 m 2 / g; the particle size of titanium dioxide B is 10-15nm, and the specific surface area is 30-40m 2 / g; the particle size of titanium dioxide C is 50-60nm, and the specific surface area is 40-50m 2 / g. Purchased from Beijing Dekedao Gold Technology Co., Ltd.
[0082] Comparative Example 3
[0083] The difference between this comparative example and Example 1 is that the titanium dioxide comprises titanium dioxide A, titanium dioxide B and titanium dioxide C in a weight ratio of 0.4:1:1.5; the titanium dioxide A has a particle size of 90-100 nm and a specific surface area of 35-45 m 2 / g; the particle size of titanium dioxide B is 70-80nm, and the specific surface area is 15-25m 2 / g; the particle size of titanium dioxide C is 110-120nm, and the specific surface area is 20-30m 2 / g. Purchased from Beijing Dekedao Gold Technology Co., Ltd.
[0084] Comparative Example 4
[0085] The difference between this comparative example and Example 1 is that the modifier is glycidyl methacrylate, maleic anhydride and isocyanate in a weight ratio of 1:1:1.
[0086] Comparative Example 5
[0087] The difference between this comparative example and Example 1 is that the modified fiber-forming resin is replaced by polyethylene terephthalate II.
[0088] Comparative Example 6
[0089] The difference between this comparative example and Example 1 is that the modified nano silver antibacterial powder is not modified.
[0090] Comparative Example 7
[0091] The difference between this comparative example and Example 1 is that the preparation method of the modified nano-silver antibacterial powder comprises the following steps: mixing nano-silver antibacterial powder, silane coupling agent KH550, ethanol and deionized water in a weight ratio of 1:0.3:17:32, heating and stirring at 72°C for 2.5h, cooling, filtering, washing and drying to obtain modified nano-silver antibacterial powder.
[0092] Performance Testing
[0093] The textiles prepared in Examples 1-2 and Comparative Examples 1-7 were subjected to performance tests.
[0094] (1) Strength test: in accordance with GB / T3923.2-2013 “Tensile properties of textile fabrics - Part 2: Determination of breaking strength (grab method)”.
[0095] (2) Anti-ultraviolet performance test: The national standard for the test is GB / T18830-2009 Evaluation of the anti-ultraviolet performance of textiles. The fabrics were cut into samples of 5 mm × 5 mm in size and tested using a UV-visible spectrometer Lambda35 (UVVis). The wavelength scanning range was set to 200-400 nm and the scanning wavelength interval was 1 nm. The cut samples were washed 100 times with clean water under the same parameters and then tested for the ultraviolet protection factor (UPF) before and after washing.
[0096] (3) Antibacterial property test: According to GB / T20944.2-2007 “Evaluation of antibacterial properties of textiles Part 2: Absorption method”, the antibacterial properties of the textiles against Escherichia coli were tested before washing and after washing 50 times at 40°C.
[0097] (4) Water vapor permeability test: measured in accordance with GB / T12704-1991.
[0098] Table 1 Performance test results
[0099]
[0100] From the above performance test results, it can be seen that the textiles of Examples 1-2 have excellent anti-ultraviolet, antibacterial, moisture permeability and tensile strength effects, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect of each component.
[0101] However, the comparative examples are significantly worse than the embodiments in the corresponding performance tests because the necessary technical solutions are not adopted. In comparative example 1, the modification method of titanium dioxide is changed, and it can be seen from the results that the anti-ultraviolet effect of the textile is reduced; in comparative example 2, the ratios of titanium dioxide A, titanium dioxide B and titanium dioxide C are different, and it can be seen from the results that the anti-ultraviolet effect of the textile is reduced; in comparative example 3, the particle sizes of titanium dioxide A, titanium dioxide B and titanium dioxide C are different, and it can be seen from the results that the anti-ultraviolet effect after washing is reduced, and the moisture permeability effect is reduced; in comparative example 4, the composition of the modifier is different, the breaking strength of the textile is reduced, and the anti-ultraviolet effect after washing is reduced; in comparative example 5, the fiber-forming resin is not modified, and the breaking strength of the textile is reduced; in comparative example 6, the nano-silver antibacterial powder is not modified, and the modification method of the nano-silver antibacterial powder in comparative example 7 is different, and it can be seen that the antibacterial effect is reduced. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0102] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a sweat-proof quick-drying textile containing a silver ion antibacterial agent, characterized in that: The following steps are involved: (1) Preparation of modified polyester fiber: The preparation method of modified polyester fiber comprises the following steps: S1: Blending modified titanium dioxide, modified nano silver antibacterial powder and polyethylene terephthalate I in a weight ratio of (2-3): (1-2): 15 at a blending temperature of 260-265° C., extruding with a screw extruder at an extrusion temperature of 200-210° C. and a screw speed of 100-200 rpm, and pelletizing to obtain a modified masterbatch; S2: blending the modified masterbatch and the modified fiber-forming resin in a weight ratio of (2-5):100, spinning, and obtaining modified polyester fibers; (2) Modified polyester fiber and cotton fiber are blended in a weight ratio of 100:(35-45) to obtain blended yarn, and the blended yarn is used as warp yarn and weft yarn for weaving to obtain sweat-proof quick-drying textiles containing silver ion antibacterial agent.
2. The method for preparing the anti-perspiration quick-drying textile containing a silver ion antibacterial agent according to claim 1, characterized in that: The yarn count of the blended yarn is 50S, wherein the warp yarn density is 130-150 yarns / inch and the weft yarn density is 55-60 yarns / inch.
3. The method for preparing the anti-perspiration quick-drying textile containing a silver ion antibacterial agent according to claim 1, characterized in that: The spinning conditions are: spinning temperature 270-300°C, spinning speed 2500-3500 m / min.
4. The method for preparing the anti-perspiration quick-drying textile containing a silver ion antibacterial agent according to claim 1, characterized in that: The preparation method of the modified titanium dioxide comprises the following steps: S1: Mix titanium dioxide, ethanol aqueous solution and silane coupling agent KH570 in a weight ratio of 1: (10-15): (0.02-0.05), stir at 50-60° C. for 3-5 hours, filter, wash and dry to obtain silane-modified titanium dioxide; S2: Mix silane-modified titanium dioxide, epoxy fatty acid methyl ester and ethyl acetate in a weight ratio of 1:(0.2-0.4):(3-4), heat to 76-78°C for reaction for 1-2h, filter, wash with anhydrous ethanol 2-3 times, and dry to obtain modified titanium dioxide.
5. The method for preparing the anti-perspiration quick-drying textile containing a silver ion antibacterial agent according to claim 4, characterized in that: Titanium dioxide includes titanium dioxide A, titanium dioxide B and titanium dioxide C in a weight ratio of (0.3-0.5):1:(1.3-1.6); the particle size of titanium dioxide A is 2-7nm, and the specific surface area is 20-30m 2 / g; the particle size of titanium dioxide B is 10-15nm, and the specific surface area is 30-40m 2 / g; the particle size of titanium dioxide C is 50-60nm, and the specific surface area is 40-50m 2 / g.
6. The method for preparing the anti-perspiration quick-drying textile containing a silver ion antibacterial agent according to claim 1, characterized in that: The preparation method of the modified fiber-forming resin comprises the following steps: mixing 6 parts by weight of polyethylene terephthalate II, 30-35 parts by weight of m-methylphenol and 1-1.5 parts by weight of a modifier, stirring and reacting at 30-35° C. for 50-60 minutes to obtain the modified fiber-forming resin.
7. The method for preparing the anti-perspiration quick-drying textile containing a silver ion antibacterial agent according to claim 6, characterized in that: The modifier is glycidyl methacrylate, maleic anhydride and isocyanate in a weight ratio of 1: (1.4-1.6): (0.2-0.5).
8. The method for preparing the anti-perspiration quick-drying textile containing silver ion antibacterial agent according to claim 1, characterized in that: The preparation method of the modified nano silver antibacterial powder comprises the following steps: (1) mixing nano silver antibacterial powder, silane coupling agent KH550, ethanol and deionized water, heating and stirring at 70-75° C. for 2-3 hours, cooling, filtering and washing to obtain silane-modified powder; (2) Mixing silane-modified powder, nano-polytetrafluoroethylene, polyvinyl alcohol and 45-50% by weight ethanol aqueous solution in a weight ratio of 1: (10-15): (0.1-0.4): (60-80), dispersing them uniformly, and then spray drying them to obtain modified nano-silver antibacterial powder.
9. The method for preparing the anti-perspiration quick-drying textile containing a silver ion antibacterial agent according to claim 8, characterized in that: The weight ratio of the nano silver antibacterial powder, the silane coupling agent KH550, ethanol and deionized water is 1: (0.2-0.4): (15-20): (30-35).
10. An anti-perspirant quick-drying textile containing a silver ion antibacterial agent prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Novel sweat stain prevention fabric
CN114059218A